Bone density at the os calcis: reference values, reproducibility, and effects of fracture history and physical activity. Issue 1 (21st December 2004) - Chinn, D J; Fordham, J N; Kibirige, M S; Crabtree, N J; Venables, J; Bates, J; Pitcher, O
Abstract : Aims: To establish reference values for bone mineral density (BMD) measured at the os calcis (OC) in healthy UK Caucasian children. Secondary objectives were to assess the reproducibility of the measurement and the effects of fracture history and habitual physical activity. Methods: A total of 403 children aged 5–18 were studied. Main outcome measures were: BMDoc measured by peripheral DXA, total BMD measured by whole body axial scanner, age, anthropometry, pubertal status, self-reported fracture history, and physical activity (PA) expressed as a three point score. Results: Complete data were available on 171 girls and 123 boys free of a history of fracture. BMDoc was related positively to age, body size, and total BMD, and could be predicted using a proportional model based on height alone (R 2 : 65% girls, 77% boys). Mean BMDoc appears to plateau in girls at 15 years and attain a value that concurs with the mean peak value in adult women. The 95% limits of agreement in repeated measures were −0.029 to 0.029 g/cm 2 (n = 53). Compared with sedentary children, those doing regular sports or PA for more than five hours a week had an increased BMDoc (by about 0.03 g/cm 2 or about 7% of the overall mean). A history of fracture (n = 81) was associated with a reduced BMDoc in boys but not in girls, though our study may have been underpowered for a subgroup analysis. Conclusions: BMDoc can be measured easily and quickly in children older than 5 years and provides an objective measure of areal bone density for clinical and research studies using a reference range derived from its relation to height.